THE SCIENTIFIC APPROACH IN TEACHING WRITING BY USING GUIDED WRITING BASED ON CURRICULUM 2013 - Indahtriyani, Oktavia Erwinarti; Sada, Clarry; Sutapa, Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The study presented of how students are taught by using guided writing. It showed the implementation of the scientific approach in teaching and learning process particularly in teaching writing. This research applies a CAR (classroom action research) to the tenth grade students of Computer and Networking Program of SMKN 1 Bengkayang in Academic Year 2014/2015.  The Classroom Action Research was conducted in three cycles. Each cycles consisted of four steps: planning, action, observation and reflection. In collecting the data, the researcher used test, observation checklist, questionnaires, and photograph or documents of students writing product. The result of the research shows that guided writing could improve the students? writing skill. Through guided writing, the students showed great interest and actively involved in the teaching and learning process. The students were able to construct sentences correctly. In this case, the sentences they constructed were based on the researcher?s explanation and examples. They also used more vocabularies in their writing. The study showed that there was an improvement on the students? writing skill. The researcher suggests that English teacher is better to implement scientific approach helped by guided writing in their class in order to help the students improve their writing skill. Keywords: Curriculum 2013, Scientific Approach, Guided Writing Abstrak : Penelitian ini membahas tentang implementasi pendekatan saintifik dengan menggunakan teknik Guided Writing pada pengajaran writing. Penelitian ini adalah penelitian tindakan kelas pada kelas X Jurusan Teknik Komputer dan Jaringan SMK Negeri 1 Bengkayang tahun ajaran 2014/2015. Penelitian ini dilakukan dalam tiga siklus. Masing-masing siklus nya terdiri dari empat langkah yaitu: perencanaan, pelaksanaan, pengamatan dan refleksi. Pada pengumpulan data kualitatif, peneliti menggunakan data penilaian observasi, dokumentasi dan dokumen-dokumen seperti hasil menulis siswa. Pada pengumpulan data kuantitatif, peneliti memberikan soal tes di setiap akhir masing-masing siklus. Dari hasil tersebut, maka penelitian ini menunjukan bahwa teknik Guided Writing dapat meningkatkan hasil belajar siswa. Dengan menggunakan teknik ini pula, siswa dapat berperan aktif dalam proses belajar mengajar di kelas. Dalam hal ini, siswa dapat menulis kalimat dengan benar berdasarkan penjelasan dan contoh-contoh yang diberikan peneliti. Kata kunci: Kurikulum 2013, Pendekatan Saintifik, Guided Writing